SUBSTITUSI MARGARIN DENGAN MINYAK BABI PADA PROSES PEMBUATAN KUE PIA - Meigasari, Made; Putra, Nengah Kencana; Hapsari, Ni Made Indri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 1 (2016): Jurnal ITEPA, 2016)
This study aims to determine the effect of subtitution of margarine with lard on the characteristic of pia cakes and to determine the concentration substitution of margarine with lard that can produce the best characteristic of pia cakes. This study used a Randomized Block Design (RBD) with the formulation of pia cakes with margarine : lard P0 (100% : 0%), P1 (75 % : 25%), P2 (50% : 50%), P3 (25% : 75%), P4(0% : 100%). The results showed there were substitution margarine with lard in the process  making of  pia cakes significant effects on  the moisture content, ash content, fat content and carbohydrate content but there were no significant effects on protein. Hedonic sensory evaluation substitution margarine with lard in the process  making of  pia cakes that includes significant effects on  the color, texture, aroma, flavor, overall acceptance of test score significant effects on the level of crispness  and aroma lard. The formulation of 25% margarine : 75% lard can produce the best characteristic of pia cakes with moisture content (13,60%),  ash content (0,73%), protein content (9,38%), fat content (26,20%), carbohydrate (50,67%) as well as hedonic sensory evaluation that includes color 5,5 (somewhat like), texture 5,85 (like), aroma 5,45(somewhat like), flavor 6,1 (like), overall acceptance 6,10 (like) and score test on the level of crispness was 4,20 (rather crispy), aroma lard  4,45 (mildly flavored lard).
Keywords: margarine, lard, pia cakes